Material for battery, method for manufacturing the same, and battery
By preloading metal atoms and oxygen atoms on the active material of lithium-ion batteries, the problem of low efficiency of the elemental silicon negative electrode material is solved, and a significant improvement in battery performance is achieved.
Patent Information
- Application Number
- CN202410631808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The Coulombic efficiency of the elemental silicon anode material used in existing lithium-ion batteries is low, resulting in poor battery performance. The existing improved methods such as the reduction reaction using inert metals has practical problems, making it difficult to truly improve Coulombic efficiency.
By preloading one or more metal atoms on the active material of the battery, it binds to oxygen atoms on the surface of the active material during charging and discharging of the battery to form a complex, and avoiding oxygen atoms from trapping lithium ions, thereby improving Coulomb efficiency.
It significantly improves the Coulomb efficiency of the battery, improves the electrochemical performance, and enhances the energy density and reversibility of the battery.
Smart Images

Figure CN118538890B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a material for a battery, a method for manufacturing the same, and a battery. Background Art
[0002] The existing structure and geometry of some rechargeable battery electrodes involve coating active materials on aluminum foil for positive electrode and copper foil for negative electrode. In order to achieve higher energy density of the battery, high-capacity negative electrode materials (e.g., silicon) must be used. During the lithiation process, lithium and silicon form lithium-silicon alloys, resulting in volume expansion of up to 400%, which can lead to cracking and degradation of the electrode structure. This is one of the main obstacles to improving the energy density of some rechargeable batteries (e.g., lithium-ion batteries).
[0003] Lithium-ion batteries (LIBs) are used in many portable electronic products, power tools, and electric and internal combustion vehicles, among others. Typically, LIBs can be composed of a lithium-containing cathode material and a lithium-accepting anode material. During charging, lithium is transferred from the cathode to the anode. During discharge, some lithium is transferred back to the cathode. Coulombic efficiency is defined as the ratio of lithium ions removed in each cycle during discharge to the lithium ions transferred to the anode during charging.
[0004] Until now, LIBs have been the main option for renewable energy battery applications, which require fairly large energy storage systems. However, the materials used in current LIBs generally have low storage capacity, so only a small amount of energy can be stored per charge, resulting in unsatisfactory battery performance.
[0005] CN 105399100 A discloses a method for preparing nanoporous silicon. A precursor Mg2Si / Mg composite material is prepared by alloying silicon powder and magnesium powder, and the obtained product is pickled for dealloying. However, during the pickling process, water molecules will inevitably react with silicon element and irreversibly oxidize the silicon element. During charging, its silicon oxide forms an irreversible product with lithium ions, which has a negative impact on coulomb efficiency.
[0006] CN114597375A proposes a method of reducing silicon oxide with a highly inert metal element (e.g., silver, copper, nickel, iron, and cobalt) to reduce the oxidation degree of elemental silicon and improve the coulombic efficiency of the elemental silicon negative electrode. However, the price of these inert metals (e.g., silver) is too high, which is not conducive to the large-scale production and commercialization of elemental silicon negative electrode materials.
[0007] CN115053364A increases the coulombic efficiency by adding zirconium metal to silicon, but this method can only increase the coulombic efficiency by 2%, with little effect.
[0008] The above three patents, which use various inert metal elements to reduce porous or nano silicon, have practical problems and are difficult to truly improve the coulombic efficiency of silicon. Summary of the invention
[0009] In view of the shortcomings of the prior art, one object of the present invention is to provide a material for a battery, which has high coulombic efficiency and excellent electrochemical performance. Another object of the present invention is to provide a battery comprising the above material. Another object of the present invention is to provide a method for manufacturing the above material.
[0010] According to a first aspect of the present invention, the present invention provides a material for a battery, comprising:
[0011] an active material configured to chemically react during charging and / or discharging of the battery; and
[0012] One or more metal atoms, the one or more metal atoms configured to hold one or more oxygen atoms of the active material and to deactivate one or more oxygen atoms of the active material during charging and / or discharging of the battery.
[0013] According to the material of the present invention, preferably, the metal atom forms a complex with the active material.
[0014] According to the material of the present invention, preferably, the metal atom is arranged to be bonded to the oxygen atom on the surface of the active material within the complex.
[0015] According to the material of the present invention, preferably, the metal atoms are bonded to oxygen atoms on the surface of the active material through covalent bonds.
[0016] According to the material of the present invention, preferably, the metal atoms remain bonded to the oxygen atoms during charging and / or discharging of the battery.
[0017] According to the material of the present invention, preferably, the metal atoms react with the oxygen atoms to form oxides within the complex.
[0018] According to the material of the present invention, preferably, the oxide forms at least one of an amorphous material and a polycrystalline material.
[0019] According to the material of the present invention, preferably, the metal atoms hold the oxygen atoms and deactivate the oxygen atoms, thereby improving the Coulombic efficiency of the material.
[0020] According to the material of the present invention, preferably, the metal atom is selected from one or more of Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce and Hf.
[0021] According to the material of the present invention, preferably, the metal atoms are embedded in the active material, thereby holding the oxygen atoms and deactivating the oxygen atoms.
[0022] According to the material of the present invention, preferably, the metal atoms are embedded in the active material in at least one of the following forms: metal element, metal oxide, metal hydroxide, metal acetate, metal nitrate, metal sulfate and metal carbonate.
[0023] According to the material of the present invention, preferably, the active material is selected from one or more of metalloid elements, oxides of metalloid elements, metal elements and oxides of metal elements.
[0024] According to the material of the present invention, preferably, the metalloid element is Si and / or B.
[0025] According to the material of the present invention, preferably, the active material is Si and includes SiO x and SiO2; wherein 0 <x<2。
[0026] According to the material of the present invention, preferably, the active material is in a granular form, and the particle size of the active material is 5 nm to 5 mm.
[0027] According to the material of the present invention, preferably, the active material is used as a negative electrode material in the battery.
[0028] According to another aspect of the present invention, the present invention provides a battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is formed of the above-mentioned material, and the electrolyte is in ion communication with the negative electrode and the positive electrode.
[0029] According to the battery of the present invention, preferably, during charging of the battery, the metal ions of the positive electrode are transferred to the negative electrode, and during discharging of the battery, the metal ions are transferred back to the positive electrode.
[0030] According to the battery of the present invention, preferably, during discharge of the battery, the metal ions are not captured by oxygen atoms in the negative electrode.
[0031] According to the battery of the present invention, preferably, the metal ions are selected from one or more of Li, Na, K, Ca and Mg.
[0032] According to another aspect of the present invention, the present invention provides a method for manufacturing the above-mentioned material for a battery, comprising the following steps:
[0033] One or more metal atoms are preloaded onto an active material; wherein the active material is configured to undergo a chemical reaction during charging and / or discharging of a battery, and wherein the metal atoms are configured to retain and deactivate one or more oxygen atoms on a surface of the active material during charging and / or discharging of the battery.
[0034] According to the method of the present invention, preferably, the metal atoms are preloaded onto the active material by the following method:
[0035] The active material and the material containing the metal atoms are annealed at an annealing temperature of 500° C. to 1200° C. in at least one atmosphere selected from helium, nitrogen and argon, thereby preloading the metal atoms on the active material.
[0036] According to the method of the present invention, preferably, when the annealing temperature is increased, the coulombic efficiency of the battery is improved.
[0037] According to the method of the present invention, preferably, the metal atoms are preloaded onto the active material by the following method:
[0038] The active material and the material containing the metal atoms are subjected to high-energy ball milling, the active material and the material containing the metal atoms are mixed, and then heat-treated in at least one atmosphere selected from helium, nitrogen, and argon. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the porous silicon particles obtained in Example 1.
[0040] Figure 2 This is the pore size distribution diagram of the porous silicon particles obtained in Example 1.
[0041] Figure 3 This is the X-ray diffraction pattern of the material for battery obtained in Example 1.
[0042] Figure 4 This is the X-ray diffraction pattern of the material for battery obtained in Example 2.
[0043] Figure 5 This is the X-ray diffraction pattern of the material for battery obtained in Example 3. DETAILED DESCRIPTION
[0044] Through research, testing and experimentation, we have found that metalloids and metalloid oxides such as silicon-based materials are potential high-capacity anodes for lithium-ion batteries. However, high-surface-area metalloid (e.g., Si) particles are highly reactive and, after charging into the lattice, metalloids (e.g., Li xSi) can react with the electrolyte and trap lithium within the material, reducing the overall reversibility of lithium insertion and deinsertion.
[0045] During the charging process, lithium ions (Li + ) can be stored by reacting with Si and releasing lithium ions during discharge. Ideally, the coulombic efficiency of the negative electrode should be close to 100%, that is, the amount of lithium ions reaching the negative electrode should be the same as the amount of lithium ions removed. If lithium ions are trapped at the negative electrode, the coulombic efficiency will be less than 100%. The available capacity and energy density of the battery depend on the amount of reversible lithium ions, and the available capacity and energy density of the battery become lower.
[0046] We have found that oxygen on the surface of the negative electrode material has a negative impact on the charge and discharge process. In particular, some oxygen will deactivate Si, which will reduce the total amount of Li that can be inserted and thus reduce the storage capacity. During the lithiation process (i.e., the charging process), some oxygen will also react with lithium and form irreversible products during the lithiation process, in which Li is trapped, thereby reducing the reversibility of Li ions, i.e., the first coulombic efficiency of the material. Some oxygen will gradually dissolve into the electrolyte, which will have an adverse effect on the coulombic efficiency of the material. Therefore, lithium is mainly captured by oxygen in the lattice, offsetting the benefits of the higher capacity of the active material.
[0047] <Materials for Batteries>
[0048] Based on the above findings, the present invention provides a material for a battery, comprising: an active material and one or more metal atoms, wherein the active material is configured to undergo a chemical reaction during the charging and / or discharging of the battery; and the one or more metal atoms are configured to keep one or more oxygen atoms on the surface of the active material and inactivate one or more oxygen atoms on the surface of the active material during the charging and / or discharging of the battery. The battery of the present invention is preferably a lithium ion battery. This can prevent lithium from being captured by oxygen in the lattice, thereby improving the coulombic efficiency of the material. The active material of the present invention can be used as a negative electrode material for a battery.
[0049] In the material of the present invention, the metal atom and the active material can form a complex. This is conducive to improving the stability of the material. The active material has oxygen atoms on its surface. In the complex, the metal atom is combined with the oxygen atoms on the surface of the active material. In some embodiments, the metal atom can be combined with the oxygen atoms on the surface of the active material through a covalent bond. In some embodiments, the metal atom can be combined with the oxygen atoms on the surface of the active material through a coordination bond.
[0050] According to a preferred technical solution of the present invention, during the charging and / or discharging of the battery, the metal atom remains combined with the oxygen atom. This can effectively avoid or reduce the capture of lithium by oxygen in the lattice. The metal atom can react with the oxygen atom to form an oxide in the complex. The oxide of the present invention forms an amorphous material and / or a polycrystalline material. The metal atom holds the oxygen atom and inactivates the oxygen atom, thereby improving the Coulomb efficiency of the material. Specifically, the metal atom is embedded in the active material, thereby holding the oxygen atom and inactivating the oxygen atom.
[0051] In some embodiments, the surface of the active material has an oxide formed by the active material and oxygen atoms, and at least a portion of the oxygen atoms in the oxide are combined with metal elements. Specifically, at least 50% of the oxygen atoms on the surface of the active material are combined with metal elements; preferably, at least 80% of the oxygen atoms on the surface of the active material are combined with metal elements; more preferably, at least 90% of the oxygen atoms on the surface of the active material are combined with metal elements. In some embodiments, all oxygen atoms on the surface of the active material are combined with metal elements.
[0052] The mass ratio of active material to metal atom may be 10:(0.2-5); preferably 10:(0.5-3); more preferably 10:(0.8-2). In certain embodiments, the mass ratio of active material to metal atom is 10:(1-1.2). The mass of metal atom is calculated as the mass of its oxide.
[0053] Metal Atoms
[0054] The metal atom of the present invention can be selected from one or more of alkali metal elements, alkaline earth metal elements, group IIIA elements, group IIIB elements, and group IVB elements. Examples of alkali metal elements include, but are not limited to, Na, K, Rb, and Cs. Preferably, the alkali metal element is K. Examples of alkaline earth metal elements include, but are not limited to, Ca, Mg, and Sr. Preferably, the alkaline earth metal element is Ca. Examples of group IIIA elements include, but are not limited to, Al and Ga. Preferably, the group IIIA element is Al. Examples of group IIIB elements include, but are not limited to, Sc, Y, and lanthanides. Examples of lanthanides include, but are not limited to, La and Ce. Preferably, the group IIIB element is Y. Examples of group IVB elements include, but are not limited to, Ti and Zr. Preferably, the group IVB element is Zr.
[0055] According to one embodiment of the present invention, the metal atom is a combination of an alkaline earth metal element, an alkali metal element and a group IVB element. The mass ratio of the alkaline earth metal element, the alkali metal element and the group IVB element can be (0.1-1):(0.1-1):1; preferably (0.2-0.8):(0.2-0.8):1; more preferably (0.3-0.6):(0.3-0.6):1. The mass of each of the above elements is calculated as the mass of its oxide.
[0056] According to another embodiment of the present invention, the metal atom is a Group IIIB element.
[0057] According to another embodiment of the present invention, the metal element is a combination of a group IIIA element and an alkali metal element. The mass ratio of the group IIIA element to the alkali metal element may be (0.5-2):1; preferably (0.8-1.5):1; more preferably (1-1.2):1. The mass of each of the above elements is calculated as the mass of its oxide.
[0058] In the material of the present invention, the metal atom is selected from one or more of Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce and Hf. In certain embodiments, the metal atom is selected from one or more of Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La and. In a preferred embodiment, the metal atom is selected from one or more of K, Ca, Zr, Al and Y. According to one embodiment of the present invention, the metal atom is a combination of K, Ca and Zr. According to another embodiment of the present invention, the metal atom is Y. According to yet another embodiment of the present invention, the metal atom is a combination of K and Al.
[0059] In the material of the present invention, the metal atom can be provided by its metal element or its compound. The compound of the metal atom can be selected from one or more of metal oxides, metal hydroxides, metal acetates, metal nitrates, metal sulfates and metal carbonates. These substances can all be commercially available products. In certain embodiments, the metal atom is embedded in the active material in at least one of the following forms: metal element, metal oxide, metal hydroxide, metal acetate, metal nitrate, metal sulfate and metal carbonate. Preferably, the metal oxide form is embedded in the active material.
[0060] Active Materials
[0061] In the materials of the present invention, the active material is preferably a metalloid (Me)-based material. The active material may be selected from one or more of metalloid elements, oxides of metalloid elements, metal elements, and oxides of metal elements. The metalloid element is preferably Si and / or B. Specific examples of the metalloid (Me)-based material include, but are not limited to, silicon-based materials and boron-based materials. In certain embodiments, the active material is silicon and includes at least one of SiO x and SiO2; wherein, 0 < x < 2. According to one embodiment of the present invention, the active material is a silicon-based material containing SiO x ; wherein, 0 < x < 2. According to another embodiment of the present invention, the active material is a silicon-based material containing SiO2. According to still another embodiment of the present invention, the active material is a silicon-based material containing SiO x and SiO2; wherein, 0 < x < 2.
[0062] The active material of the present invention is preferably a silicon-based material, and has at least one of SiO x and SiO2 on the surface of the active material; wherein, 0 < x < 2. According to one embodiment of the present invention, the active material is a silicon material having a pore structure inside and / or on the surface (hereinafter also referred to as "porous silicon material").
[0063] In the materials of the present invention, the active material may be granular, and the particle size of the active material is 5 nm to 5 mm, preferably 500 nm to 50 μm, more preferably 1 to 30 μm, and most preferably 1 to 5 μm. The particle size can be measured by conventional methods. The present invention finds that using micron-sized active materials is more beneficial to improving the Coulomb efficiency of the materials.
[0064] The silicon-based material of the present invention may be porous silicon particles, for example, porous amorphous silicon particles and / or porous polycrystalline silicon particles. The particle size of the porous silicon particles of the present invention is preferably 500 nm to 50 μm, preferably 1 to 5 μm. Using micron-sized porous silicon particles is beneficial to improving the Coulomb efficiency of the materials.
[0065] The porous silicon particles of the present invention can be provided by a porous silicon material. A porous silicon material can be prepared by using an alloy reaction of magnesium metal and silicon metal and a vacuum distillation dealloying method. The manufacturing method of the porous silicon material and other related equipment and methods are introduced below.
[0066] The manufacturing method of the porous silicon material of the present invention includes the following steps:
[0067] (i) Put the alloy material and silicon particles into a furnace, evacuate the air in the furnace, and then fill it with an inert gas;
[0068] (ii) heating the alloy material and silicon particles to 1000-1300° C., keeping the temperature for 1-6 hours, and taking out the alloy after natural cooling and crushing it;
[0069] (iii) placing the crushed alloy in a vacuum furnace, evacuating the gas in the furnace, heating the furnace to 700-950° C., and performing vacuum distillation to de-alloy the alloy to obtain a porous silicon material.
[0070] In step (i), the air in the furnace can be pumped out with an air pump. The air pressure in the furnace is equivalent to 0.01% of atmospheric pressure. The alloy material may include at least one of zinc, magnesium, calcium, strontium, barium, boron, phosphorus, lithium and iron. The silicon content in the alloy material and silicon particles is about 20 to 99 mol%. The mass ratio of silicon particles to alloy material can be 33: (40 to 90); preferably 33: (50 to 80); more preferably 33: (60 to 70). The inert gas can be selected from one or more of nitrogen, argon, helium and neon. According to one embodiment of the present invention, the inert gas is argon.
[0071] In step (ii), the heating temperature is preferably 1100 to 1250° C., more preferably 1100 to 1150° C. The holding time is preferably 2 to 5 hours, more preferably 2 to 3 hours.
[0072] In step (iii), all gases in the furnace are pumped out by a molecular pump. For example, the gas pressure in the furnace is equivalent to 0.001% of atmospheric pressure. The heating temperature is preferably 750-850°C, more preferably 800-830°C.
[0073] The alloy material is assumed to be metal magnesium for the purpose of illustration.
[0074] (i) placing metallic magnesium and silicon particles into a furnace, evacuating the air in the furnace, and then filling it with argon gas as an inert protective atmosphere;
[0075] (ii) heating magnesium and silicon particles to 1000-1300° C., keeping the temperature for 1-6 hours, and taking out the magnesium-silicon alloy after natural cooling and crushing it;
[0076] (iii) placing the crushed magnesium-silicon alloy in a vacuum furnace, extracting the gas in the furnace, heating the furnace to 700-950° C., and performing vacuum distillation to de-alloy the alloy to obtain a porous silicon material.
[0077] The porous silicon material is ground to form porous silicon particles. The grinding can be ball milling. The grinding balls used in the ball milling can be zirconia balls. The diameter of the grinding balls can be 0.5 to 5 cm; preferably 1 to 3 cm. The ball-to-material ratio can be (3 to 9):1; preferably (4 to 8):1; more preferably (5 to 7):1. The ball milling can be carried out at a rotation speed of 200 to 700 rpm; preferably 300 to 500 rpm. The ball milling time can be 0.5 to 5 hours; preferably 1 to 3 hours; preferably 1.5 to 2 hours.
[0078] In certain embodiments, the porous silicon material is placed in a zirconia ball mill, zirconia balls are added at a weight ratio of 1:5-6 (material: ball), and the material is ground at a speed of 300-500 rpm for 1.5-2 hours to obtain porous silicon particles with a particle size of 1-5 μm.
[0079] In a broad embodiment, the present invention provides an apparatus for producing porous silicon material from silicon particles, comprising:
[0080] (i) a device for alloying silicon particles with an alloy material to form an alloy;
[0081] (ii) an apparatus for casting the alloy into alloy sheets, strips or films; and
[0082] (iii) An apparatus for extracting alloy material from an alloy sheet, strip or film to form a porous silicon material.
[0083] In another broad embodiment, the present invention provides a method for producing hydrogen, comprising the steps of:
[0084] (i) alloying at least one of a silicon raw material and an aluminum raw material with an alloy material to form an alloy;
[0085] (ii) casting the alloy into alloy sheets, strips or films;
[0086] (iii) extracting the alloy sheet, strip or membrane to form at least one of a porous silicon sheet, strip or membrane and a porous aluminum sheet, strip or membrane; and
[0087] (iv) allowing at least one of a porous silicon sheet, tape or membrane and a porous aluminum sheet, tape or membrane to interact with an aqueous solution to generate hydrogen through said interaction.
[0088] In step (i), the alloy material may include at least one of zinc, magnesium, calcium, strontium, barium, boron, phosphorus, lithium and iron. Other impurities in the alloy do not cause major differences in hydrogen production performance. Step (i) can produce an alloy containing about 20 to 99 mol% silicon. Preferably, step (i) can produce an alloy containing about 60 mol% silicon.
[0089] In yet another broad embodiment, the present invention provides a method for preparing at least one of a porous silicon sheet, tape or membrane and a porous aluminum sheet, tape or membrane for hydrogen production by interaction with a solution containing H2O, the method comprising the steps of:
[0090] (i) alloying at least one of a silicon raw material and an aluminum raw material with an alloy material to form an alloy;
[0091] (ii) casting the alloy into alloy sheets, strips or films; and
[0092] (iii) extracting the alloy sheet, strip or membrane to form at least one of the porous silicon sheet, strip or membrane and the porous aluminum sheet, strip or membrane.
[0093] The above-mentioned H2O-containing solution may be alkaline in nature.
[0094] In yet another broad embodiment, the present invention provides a method for producing hydrogen, the method comprising the steps of:
[0095] (i) alloying at least one of a silicon raw material and an aluminum raw material with an alloy material to form an alloy;
[0096] (ii) casting the alloy into alloy sheets, strips or films;
[0097] (iii) extracting the alloy sheet, strip or membrane to form at least one of a porous silicon sheet, strip or membrane and a porous aluminum sheet, strip or membrane; and
[0098] (iv) interacting at least one of the porous silicon sheet, tape or membrane and the porous aluminum sheet, tape or membrane with an aqueous solution, preferably alkaline in nature, to generate hydrogen through said interaction.
[0099] In another broad embodiment, the present invention provides an apparatus for producing at least one of a porous silicon sheet, tape or membrane and a porous aluminum sheet, tape or membrane, wherein at least one of the porous silicon sheet, tape or membrane and the porous aluminum sheet, tape or membrane is configured to produce hydrogen upon interaction with an aqueous solution, the apparatus comprising:
[0100] (i) a device for alloying at least one of a silicon raw material and an aluminum raw material with an alloy material to form an alloy;
[0101] (ii) an apparatus for casting the alloy into alloy sheets, strips or films; and
[0102] (iii) an apparatus for extracting the alloy sheet, ribbon or membrane to form at least one of a porous silicon sheet, ribbon or membrane and a porous aluminum sheet, ribbon or membrane.
[0103] In another broad embodiment, the present invention provides a device for hydrogen production, the device comprising a device for interacting at least one of a porous silicon wafer, strip or membrane and a porous aluminum wafer, strip or membrane with an aqueous solution to generate hydrogen.
[0104] Furthermore, the present invention can produce at least one of a porous silicon wafer, strip or membrane and a porous aluminum wafer, strip or membrane according to a method comprising the following steps:
[0105] (i) Alloying at least one of a silicon raw material and an aluminum raw material with an alloying material to form an alloy;
[0106] (ii) Casting the alloy into an alloy wafer, strip or membrane; and
[0107] (iii) Extracting the alloy wafer, strip or membrane to form at least one of the porous silicon wafer, strip or membrane and the porous aluminum wafer, strip or membrane.
[0108] Figure 1 An embodiment of a material containing silicon, calcium, potassium, zirconium and oxygen is shown, and the X-ray diffraction measurement results after heat treatment show that the formed substance is potassium feldspar.
[0109] In certain embodiments, the active material is a material configured to accommodate a certain amount of metal ions to store electrical energy. For example, the active material can be porous silicon or a quasi-metal oxide (MeO), a silicon-based material SiO x (where 0 < x < 2) and / or a high-capacity silicon-based material having multiple sites that can receive a certain amount of metal ions (e.g., Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce, Hf ions) through a suitable chemical reaction between the active material and the metal ions.
[0110] During "charging" (by external current / electron supply), lithium ions attach to the vacancies on silicon in the active material to form a Si / Li alloy, and thus, lithium is "inserted" into the active material. Conversely, during "discharging" (the material supplies electrons / current to a connected device), lithium ions will separate from the Si / Li alloy. The electrolyte in contact with the active material can provide lithium ions.
[0111] Without being limited by the following examples, the active material can contain one or more metal elements (e.g., Zn, Ga, In, Sn, Pb and Bi), one or more metal oxides (e.g., ZnO, Ga2O3, Ga2O, In2O3, SnO, SnO2, PbO, Pb3O4, PbO2, Pb2O3, Pb 12 O 19, Bi2O3), one or more alloys and / or conversion materials of these metal elements. In battery applications, these materials and metal elements can react to store or release energy (preferably electrical energy).
[0112] During the "charging" process, lithium ions attach to the metal oxides in the active material and convert the metal oxides into lithium oxides and lithium metal alloys, thereby "inserting" lithium into the active material. During the "discharging" process, lithium ions are extracted into the electrolyte and the metal is converted into metal oxides.
[0113] The pre-loaded raw material contains one or more metal atoms pre-loaded into the active material through a processing technology. The precursor of the metal atom is preferably at least one of the following forms: metallic element (A), metal oxide (A-O), metal hydroxide (A-OH), metal acetate (A-CH3COOH), metal nitrate (A-NO3), metal sulfate (A-SO4), and metal carbonate (A-CO3). The precursor of the metal atom contains one or more metal atoms selected from Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce, and Hf.
[0114] The pre-loaded metal atoms act as an "adhesive" for the active material, thereby binding together multiple individual parts in the active material. The metal atoms can form complexes with the active material and bind the oxygen atoms of the active material within the complexes.
[0115] For example, the empirical formula of the material of the present invention can be expressed as A y MeO x , where A is one or more of the metal atoms selected from the group consisting of Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce, Hf; Me is a metalloid, for example, Si, B; O is oxygen; 0 < x < 4 and 0 < y < 4. The basic particle size of the material of the present invention can be 5 nm to 5 mm.
[0116] In particular, the pre-loaded metal atoms can keep the oxygen atoms of SiO x (where 0 < x < 2) within each part of the active material and deactivate the oxygen atoms of SiO x (0 < x < 2) and SiO2 within each part of the active material. Each of the metal atoms and oxygen atoms shares the electron pair between them and forms a covalent bond. Since the metal atoms are bonded to the oxygen atoms, the metal atoms remain bonded to the oxygen atoms of the active material during battery charging and / or discharging.
[0117] Now describing in detail the structure of the complex, the active material, metal atoms and oxygen atoms together form a complex. In the complex, the atoms are arranged in an ordered or disordered manner, thereby forming multiple crystalline or amorphous regions within the preloaded raw material. Therefore, the preloaded raw material loaded with metal atoms becomes an amorphous or polycrystalline material. The resulting material containing the A-Me-O formation is not reactive in an atmospheric environment.
[0118] The preloaded metal atoms hold and deactivate oxygen atoms, thereby significantly improving the Coulombic efficiency of the material of the present invention.
[0119] <Method for producing material for battery>
[0120] The method for a material for a battery of the present invention comprises the following steps: preloading one or more metal atoms onto an active material; wherein the active material is configured to undergo a chemical reaction during charging and / or discharging of the battery, and wherein the metal atoms are configured to keep one or more oxygen atoms on the surface of the active material and deactivate one or more oxygen atoms on the surface of the active material during charging and / or discharging of the battery.
[0121] Taking a metalloid (Me)-based material as an example, a small amount of metal atoms (A) selected from Na, K, Rb, Cs, Ca, Al, Mg, Sr, Sc, Y, Zr, Ti, La, Ce, and Hf are preloaded into the structure of the material. The metal atom (A) can react with oxygen (O) on the surface of the metalloid (Me)-based material and form an A-Me-O complex (i.e., an oxidation state) with the metalloid (Me). Among them, the metal atom deactivates oxygen. This can reduce the influence of oxygen and solve the problem of low Coulomb efficiency. Therefore, this will improve the electrochemical performance of the metalloid material when used in a battery.
[0122] In certain embodiments, the metal atoms are preloaded onto the active material by the following method: at an annealing temperature of 500°C to 1200°C, in at least one atmosphere selected from helium, nitrogen and argon, the active material and the material containing the metal atoms are annealed, thereby preloading the metal atoms onto the active material. In the above method, the material containing the metal atoms is a metal salt or a metal oxide. The metal salt may be a carbonate, nitrate, acetate or sulfate. The annealing temperature is preferably 800°C to 1150°C, more preferably 1000°C to 1100°C. The present invention finds that when the annealing temperature is appropriately increased, the coulombic efficiency of the battery is improved.
[0123] In other embodiments, the metal atoms are preloaded onto the active material by:
[0124] The active material and the material containing the metal atoms are ball-milled or high-energy ball-milled, the active material and the material containing the metal atoms are mixed, and then heat-treated in at least one atmosphere selected from helium, nitrogen and argon. In the above method, the material containing the metal atoms is a metal salt or a metal oxide. The metal salt may be a carbonate, a nitrate, an acetate or a sulfate. The heat treatment temperature may be 500°C to 1200°C, preferably 800°C to 1150°C, and more preferably 1000°C to 1100°C. The present invention finds that when the heat treatment temperature is appropriately increased, the coulombic efficiency of the battery is improved.
[0125] <Battery and manufacturing method>
[0126] The material of the present invention can be used in batteries. Batteries include but are not limited to lithium ion batteries, sodium ion batteries, potassium ion batteries, calcium ion batteries, magnesium ion batteries or lithium sulfur batteries. Preferably, the material of the present invention is used as a negative electrode material in a battery.
[0127] In certain embodiments, a battery structure is exemplarily provided, a negative electrode, a positive electrode, and an electrolyte ionically connected to the positive electrode and the negative electrode formed by the material of the present invention, through which ions can move during the charge and discharge cycle. The battery of the present invention may include a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is formed by the material of the present invention, and the electrolyte is ionically connected to the negative electrode and the positive electrode. In certain embodiments, during charging of the battery, the metal ions of the positive electrode are transferred to the negative electrode, and during discharging of the battery, the metal ions are transferred back to the positive electrode. During the discharge of the battery, the metal ions are not captured by the oxygen atoms in the negative electrode.
[0128] Optionally, the battery may include a separator. The separator is configured to electrically insulate the positive electrode from the negative electrode. The positive electrode is adapted to release metal ions, such as lithium, sodium, potassium, calcium, and magnesium ions. On the other hand, the negative electrode receives metal ions from the positive electrode.
[0129] During each "charge" cycle of a battery, metal ions (e.g., lithium, sodium, potassium, calcium, and magnesium ions) are transferred from the positive electrode to the negative electrode. Later, during the "discharge" phase, the metal ions present in the negative electrode are transferred back to the positive electrode.
[0130] Advantageously, the preloaded metal atoms on the material of the present invention as the negative electrode play an important role in the discharge process of metal ions. The oxygen atoms in the negative electrode combine with the preloaded metal atoms, so that the metal ions are not trapped by the oxygen atoms in the negative electrode during battery discharge, and the active material is inhibited from dissolving into the electrolyte.
[0131] The battery can be manufactured by conventional methods. The material of the present invention, conductive carbon black and sodium carboxymethyl cellulose are mixed, and an appropriate amount of deionized water is added as a solvent, and the mixture is uniformly mixed to prepare a slurry. The slurry is uniformly applied on a copper foil with a scraper, and then vacuum dried, and punched into a circular electrode sheet with a mold. The circular electrode sheet and a metal lithium sheet are assembled into a battery.
[0132] The above preparation process and the materials of the present invention are tested in combination with specific examples. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can be obtained from commercial sources.
[0133] Here is the test method:
[0134] SEM: The morphology of the powders was examined by scanning electron microscopy (SEM, Philips XL30FEG).
[0135] XRD: X-ray diffractometer (XRD, D2 Phaser Brucker) was used for testing. The scanning range was 10° to 80°, the scanning rate was 0.05° / s, and the X-ray source was CuKα ray (λ=0.154178 nm).
[0136] Electrical performance test: The materials obtained in the embodiment or comparative example, conductive carbon black (Acetylene Black) and sodium carboxymethyl cellulose were mixed in a mass ratio of 8:1:1, and an appropriate amount of deionized water was added as a solvent. The slurry was uniformly mixed in an agate mortar to prepare a slurry. The slurry was evenly applied on a copper foil with a scraper, and then vacuum dried at 80°C for 4 hours, and punched into a circular electrode sheet with a diameter of 16 mm with a mold. The circular electrode sheet was used as the research electrode, and the metal lithium sheet was used as the counter electrode, and a 2032 button battery was assembled in a glove box.
[0137] The electrochemical test was carried out using the Xinwei battery testing system, with a charge and discharge current density of 250mA / g, a charge and discharge cut-off voltage of 0.01~1V, and a test temperature of 25℃.
[0138] Example 1
[0139] 67 g of magnesium and 33 g of silicon particles were placed in a high-temperature furnace, and then the air in the furnace was evacuated to 0.01% atmospheric pressure using an air pump, and then filled with argon gas with a purity of 99.99% as an inert protective atmosphere.
[0140] The magnesium and silicon particles were heated to 1100°C and kept at this temperature for 2 hours. After natural cooling, the magnesium-silicon alloy was taken out and crushed.
[0141] The crushed magnesium-silicon alloy is placed in a vacuum furnace, and the gas in the furnace is evacuated to 0.001% atmospheric pressure using a molecular pump. The temperature is heated to 800° C. and vacuum distillation is performed to de-alloy the alloy, thereby obtaining a porous silicon material.
[0142] 10 g of porous silicon material was placed in a 50 ml zirconia ball mill, 60 g of zirconia balls with a diameter of 1 cm were added, and the mixture was ground at a speed of 400 rpm for 1.5 h to obtain porous silicon particles with a particle size of 1 to 5 μm. Figure 1 The SEM image of porous silicon particles. Figure 1 It can be seen that the porous silicon particles are irregular polygonal, with a particle size of 1 to 5 μm, and there are fewer nanoparticles. The porous structure reduces the mechanical strength of the silicon particles, and low-energy ball milling can also crush the particles to obtain powders with relatively uniform particle sizes. Figure 2 The following examples and comparative examples all adopt the above method to obtain porous silicon particles, and the performance is the same.
[0143] 0.4 g of calcium oxide, 0.4 g of potassium oxide and 1 g of zirconium oxide were added to a ball mill jar, and ball milling was performed under an argon atmosphere to obtain a composite material.
[0144] The composite material was heated to 1100°C in an argon atmosphere for 3 hours to obtain a material for a battery. The electrical properties of the obtained material are shown in Table 1.
[0145] Figure 3 This is the XRD pattern of the material for battery obtained in this example. Figure 3 The peak of the compound formed by the metal atom A and the silicon oxide layer appears, indicating that a solid-state chemical reaction occurs between the metal atom and the silicon oxide layer, proving that the present invention successfully prepares the A-Si-O porous silicon composite material.
[0146] Example 2
[0147] 67 g of magnesium and 33 g of silicon particles were placed in a high-temperature furnace, and then the air in the furnace was evacuated to 0.01% atmospheric pressure using an air pump, and then filled with argon gas with a purity of 99.99% as an inert protective atmosphere.
[0148] The magnesium and silicon particles were heated to 1100°C and kept at this temperature for 2 hours. After natural cooling, the magnesium-silicon alloy was taken out and crushed.
[0149] The crushed magnesium-silicon alloy is placed in a vacuum furnace, and the gas in the furnace is evacuated to 0.001% atmospheric pressure using a molecular pump. The temperature is heated to 800° C. and vacuum distillation is performed to de-alloy the alloy, thereby obtaining a porous silicon material.
[0150] 10 g of porous silicon material was placed in a 50 ml zirconia ball mill, 60 g of zirconia balls with a diameter of 1 cm were added, and the mixture was ground at a speed of 400 rpm for 1.5 h to obtain porous silicon particles with a particle size of 1 to 5 μm.
[0151] 1 g of yttrium oxide was added to a ball mill, and ball milling was performed under an argon atmosphere to obtain a composite material.
[0152] The composite material was heated to 1100°C in an argon atmosphere for 3 hours to obtain a material for a battery. The electrical properties of the obtained material are shown in Table 1.
[0153] Figure 4 This is the XRD pattern of the material for battery obtained in this example. Figure 4 The peak of the compound formed by the metal atom A and the silicon oxide layer appears, indicating that a solid-state chemical reaction occurs between the metal atom and the silicon oxide layer, proving that the present invention successfully prepares the A-Si-O porous silicon composite material.
[0154] Example 3
[0155] 67 g of magnesium and 33 g of silicon particles were placed in a high-temperature furnace, and then the air in the furnace was evacuated to 0.01% atmospheric pressure using an air pump, and then filled with argon gas with a purity of 99.99% as an inert protective atmosphere.
[0156] The magnesium and silicon particles were heated to 1100°C and kept at this temperature for 2 hours. After natural cooling, the magnesium-silicon alloy was taken out and crushed.
[0157] The crushed magnesium-silicon alloy is placed in a vacuum furnace, and the gas in the furnace is evacuated to 0.001% atmospheric pressure using a molecular pump. The temperature is heated to 800° C. and vacuum distillation is performed to de-alloy the alloy, thereby obtaining a porous silicon material.
[0158] 10 g of porous silicon material was placed in a 50 ml zirconia ball mill, 60 g of zirconia balls with a diameter of 1 cm were added, and the mixture was ground at a speed of 400 rpm for 1.5 h to obtain porous silicon particles with a particle size of 1 to 5 μm.
[0159] 0.5 g of aluminum oxide and 0.5 g of potassium oxide were added to a ball mill, and ball milling was performed under an argon atmosphere to obtain a composite material.
[0160] The composite material was heated to 1100°C in an argon atmosphere for 3 hours to obtain a material for a battery. The electrical properties of the obtained material are shown in Table 1.
[0161] Figure 5 This is the XRD pattern of the material for battery obtained in this example. Figure 5The peak of the compound formed by the metal atom A and the silicon oxide layer appears, indicating that a solid-state chemical reaction occurs between the metal atom and the silicon oxide layer, proving that the present invention successfully prepares the A-Si-O porous silicon composite material.
[0162] Comparative Example 1
[0163] 10 g of nano-silicon material (about 100 nm in diameter) was placed in a 50 ml zirconia ball mill, 60 g of zirconia balls with a diameter of 1 cm were added, 1 g of yttrium oxide was added to the ball mill, and ball milling was performed under an argon atmosphere at a speed of 400 rpm for 1.5 hours to obtain a composite material.
[0164] The composite material was heated to 1100°C in an argon atmosphere for 3 hours to obtain a material for a battery. The electrical properties of the obtained material are shown in Table 1.
[0165] Comparative Example 2
[0166] 67 g of magnesium and 33 g of silicon particles were placed in a high-temperature furnace, and then the air in the furnace was evacuated to 0.01% atmospheric pressure using an air pump, and then filled with argon gas with a purity of 99.99% as an inert protective atmosphere.
[0167] The magnesium and silicon particles were heated to 1100°C and kept at this temperature for 2 hours. After natural cooling, the magnesium-silicon alloy was taken out and crushed.
[0168] The crushed magnesium-silicon alloy is placed in a vacuum furnace, and the gas in the furnace is evacuated to 0.001% atmospheric pressure using a molecular pump. The temperature is heated to 800° C. and vacuum distillation is performed to de-alloy the alloy, thereby obtaining a porous silicon material.
[0169] 10g of porous silicon material was placed in a 50ml zirconium oxide ball mill, 60g of zirconium oxide balls with a diameter of 1cm were added, and the grinding was carried out at a speed of 400rpm for 1.5h to obtain porous silicon particles with a particle size of 1-5μm. The electrical properties of the obtained porous silicon particles are shown in Table 1.
[0170] Table 1
[0171]
[0172] Comparing Examples 1-3 with Comparative Example 2, preloading metal atoms can improve the first coulombic efficiency by about 2%, or even about 4%. In this field, such an increase is already very considerable. Therefore, preloading metal atoms on active materials as negative electrode materials is not something that a person skilled in the art would easily think of. Comparing Example 2 with Comparative Example 1, it can be seen that the use of micron-sized porous silicon particles instead of nano-silicon materials is more conducive to significantly improving the first coulombic efficiency, and is also conducive to improving the first charge capacity and the first discharge capacity. In view of these excellent technical effects, the use of micron-sized porous silicon particles instead of nano-silicon materials is not a conventional choice in this field. As can be seen from Table 1, the battery formed by using the material of the present invention as the negative electrode of the battery has a higher coulombic efficiency and capacity, and thus has excellent electrochemical properties.
Claims
1. A material for a battery, characterized in that: Include: an active material configured to chemically react during charging and / or discharging of the battery; and One or more metal atoms A, the one or more metal atoms A being configured to hold one or more oxygen atoms of the active material and to deactivate one or more oxygen atoms of the active material during charging and / or discharging of the battery; Wherein, the active material is a metalloid Me; the metal atom A reacts with oxygen on the surface of the metalloid Me and forms an A-Me-O complex with the metalloid Me; the metal atom A is configured to inactivate the oxygen atom; The active material is a porous silicon particle, and the active material has SiO x and SiO2; wherein 0 <x<2; Wherein, the porous silicon particles are manufactured by the following steps: The alloy material and silicon particles are placed in a melting furnace, the air in the furnace is pumped out, and then an inert gas is filled in; the alloy material and silicon particles are heated to 1000-1300°C, kept warm for 1-6 hours, and the alloy is taken out after natural cooling and crushed; the crushed alloy is placed in a vacuum furnace, the gas in the furnace is pumped out, the temperature is heated to 700-950°C, and vacuum distillation is performed to de-alloy to obtain a porous silicon material; the porous silicon material is ground to form porous silicon particles; Among them, the metal atom A is a combination of alkaline earth metal elements, alkali metal elements and Group IVB elements; the mass ratio of alkaline earth metal elements, alkali metal elements and Group IVB elements is (0.1-1):(0.1-1):1; the alkaline earth metal elements are selected from Ca, Mg, Sr, the alkali metal elements are K, and the Group IVB elements are selected from Ti and Zr.
2. The material according to claim 1, characterized in that The metal atom A is a combination of K, Ca and Zr.
3. The material according to claim 1, characterized in that The metal atom A holds the oxygen atom and deactivates the oxygen atom, thereby improving the Coulombic efficiency of the material.
4. The material according to claim 1, characterized in that The metal atoms A are embedded in the active material, thereby holding the oxygen atoms and deactivating the oxygen atoms.
5. The material according to claim 1, characterized in that The metal atom A is embedded in the active material in at least one of the following forms: a metal element, a metal oxide, a metal hydroxide, a metal acetate, a metal nitrate, a metal sulfate, and a metal carbonate.
6. The material according to claim 1, characterized in that The mass ratio of the active material to the metal atom A is 10:(0.2-5), and the mass of the metal atom A is calculated as the mass of its oxide.
7. The material according to claim 1, characterized in that The particle size of the active material is 1 to 30 μm.
8. The material according to claim 1, characterized in that The active material is used as a negative electrode material in the battery.
9. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is formed of the material according to any one of claims 1 to 8, and the electrolyte is ionically connected with the negative electrode and the positive electrode.
10. The battery according to claim 9, characterized in that During charging of the battery, the metal ions of the positive electrode are transferred to the negative electrode, and during discharging of the battery, the metal ions are transferred back to the positive electrode.
11. The battery according to claim 10, characterized in that During discharge of the battery, the metal ions are not captured by oxygen atoms in the negative electrode.
12. The battery according to claim 10, characterized in that The metal ions are selected from one or more of Li, Na, K, Ca and Mg.
13. A method for producing the material for a battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: One or more metal atoms A are preloaded onto an active material; wherein the active material is configured to undergo a chemical reaction during battery charging and / or discharging, and wherein the metal atoms A are configured to retain one or more oxygen atoms on the surface of the active material and deactivate one or more oxygen atoms on the surface of the active material during battery charging and / or discharging.
14. The method according to claim 13, characterized in that The metal atom A is preloaded onto the active material by the following method: The active material and the material containing the metal atom A are annealed at an annealing temperature of 500° C. to 1200° C. in at least one atmosphere selected from helium, nitrogen and argon, so that the metal atom A is preloaded on the active material.
15. The method according to claim 14, characterized in that When the annealing temperature is increased, the coulombic efficiency of the battery is improved.
16. The method according to claim 13, characterized in that The metal atom A is preloaded onto the active material by the following method: The active material and the material containing the metal atom A are subjected to high-energy ball milling, the active material and the material containing the metal atom A are mixed, and then heat-treated in at least one atmosphere selected from helium, nitrogen and argon.
Citation Information
Patent Citations
Preparation method for nanoporous silicon
CN105399100A
Compound and preparation method thereof as well as negative electrode prepared by adopting compound and lithium ion battery
CN106356508A
Method for preparing nano porous silicon-carbon material and pole piece
CN109950499A